Genome-wide association study identifies two loci influencing plasma neurofilament light levels - Jie-Qiong Li; Xiang-Zhen Yuan; Hai-Yan Li; Xi-Peng Cao; Jin-Tai Yu; Lan Tan; Wei-An Chen; Alzheimer's Disease Neuroimaging Initiative (BMC, 2018)
Abstract Background Plasma neurofilament light (NFL) is a promising biomarker for Alzheimer disease (AD), which increases in the early stage of AD and is associated with the progression of AD. We performed a genome-wide association study (GWAS) of plasma NFL in Alzheimer's Disease Neuroimaging Initiative 1 (ADNI-1) cohort to identify novel variants associated with AD. Methods This study included 179 cognitively healthy controls (HC), 176 patients with mild cognitive impairment (MCI), and 172 patients with AD. All subjects were restricted to non-Hispanic Caucasian derived from the ADNI cohort and met all quality control (QC) criteria. Association of plasma NFL with the genetic variants was assessed using PLINK with an additive genetic model, i.e.dose-dependent effect of the minor alleles. The influence of a genetic variant associated with plasma NFL (rs7943454) on brain structure was further assessed using PLINK with a linear regression model. Results The minor allele (T) of rs7943454 in leucine zipper protein 2 gene (LUZP2) was associated with higher plasma NFL at suggestive levels (P = 1.39 × 10− 6) in a dose-dependent fashion. In contrast, the minor allele (G) of rs640476 near GABRB2 was associated with lower plasma NFL at suggestive levels (P = 6.71 × 10− 6) in a dose-dependent effect in all diagnostic groups except the MCI group. Furthermore, the minor allele (T) of rs7943454 within LUZP2 increased the onset risk of AD (odds ratio = 1.547, confidence interval 95% = 1.018-2.351) and was associated with atrophy of right middle temporal gyrus in the whole cohort in the longitudinal study (P = 0.0234). Conclusion GWAS found the associations of two single nucleotide polymorphisms (rs7943454 and rs640476) with plasma NFL at suggestive levels. Rs7943454 in LUZP2 was associated with the onset risk of AD and atrophy of right middle temporal gyrusin the whole cohort. Using an endophenotype-based approach, we identified rs7943454 as a new AD risk locus.